Integrating Tiktok’s Duet Feature with Think Pair Share Strategy to Enhance Students’ Speaking Skill of At SMK Negeri 1 Murung Pudak Tabalong - Ulumuddin, Muhammad Ihya; Juhana, Juhana; Sundari, Hanna (JIIP - Jurnal Ilmiah Ilmu Pendidikan, 2025)
This study's findings demonstrate that the TikTok Duet and Think Pair Share methods were positively perceived by most students in Class X TKJ 2 as effective, engaging, and enjoyable tools for learning English. Perceived Usefulness of E-learning (PUE), Perceived Self-Efficacy in Utilizing E-learning (PSE), Perceived Ease of Use of E-learning (PEE), and Behavioral Intention to Use E-learning (BIE). These constructs provide a comprehensive framework for understanding why the TikTok Duet and Think Pair Share methods were well-received by students. However, the study also identified areas for improvement, particularly in addressing the needs of students who did not find these methods beneficial. This highlights the importance of considering diverse learning preferences and ensuring inclusivity in educational practices. Overall, the TikTok Duet and Think Pair Share methods have proven to be valuable tools for enhancing English learning in Class X TKJ 2. Their effectiveness lies in their ability to create an engaging and interactive learning environment that aligns with students' expectations and fosters satisfaction. However, further research and refinement are necessary to maximize their potential and ensure they cater to all students.